Phase retrieval using polychromatic illumination for transmission X-ray microscopy - Liu, Yijin (Optical Society of America, 2011)
An alternative method for quantitative phase retrieval in a transmission X-ray microscope system at sub-50-nm resolution is presented. As an alternative to moving the sample in the beam direction in order to analyze the propagation-introduced phase effect, we have illuminated the TXM using X-rays of different energy without any motor movement in the TXM system. Both theoretical analysis and experimental studies have confirmed the feasibility and the advantage of our method, because energy tuning can be performed with very high energy resolution using a double crystal monochromator at a synchrotron beam line, and there is zero motor error in TXM system in our approach. High-spatial-resolution phase retrieval is accomplished using the proposed method.